Multispecies Justice: Environmental Protection and Management Solutions - Hughes Ramadinda Etnneji; Wiwiek Awiati (Sociological Jurisprudence Journal, 2024)
This article tries to discuss the issue of "justice" by comparing the objective condition of the environment in Indonesia which continues to worsen and looking at its relationship with the concept of sustainable development and the principle of justice in the PPLH Law. This paper is of the view that the ongoing environmental crisis shows that the idea of sustainable development in practice cannot take into account environmental conditions because it focuses more on aspects of economic development. Apart from that, this condition is exacerbated because the normative meaning of the principles of justice is still "human-oriented". This article is of the view that the idea of"multispecies justice" is a solution to the current environmental crisis. To include this idea in the PPLH Law, the author uses the concept of doctrinal interpretationfrom Jezki Wroblewski to carry out legal interpretation of the principles of justice in the PPLH Law. Justice must be interpreted to include human and non-human entities or "more-than-human-oriented" justice.